1999
DOI: 10.1126/science.283.5405.1171
|View full text |Cite
|
Sign up to set email alerts
|

Novel Endotheliotropic Herpesviruses Fatal for Asian and African Elephants

Abstract: A highly fatal hemorrhagic disease has been identified in 10 young Asian and African elephants at North American zoos. In the affected animals there was ultrastructural evidence for herpesvirus-like particles in endothelial cells of the heart, liver, and tongue. Consensus primer polymerase chain reaction combined with sequencing yielded molecular evidence that confirmed the presence of two novel but related herpesviruses associated with the disease, one in Asian elephants and another in African elephants. Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
231
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(239 citation statements)
references
References 5 publications
5
231
1
2
Order By: Relevance
“…Ultérieurement, ce virus a été nommé elephantid herpesvirus 2 (ElHV2). Un autre herpèsvirus fut ensuite associé à des papillomes cutanés chez l'élé-phant d'Afrique (Jacobson et al 1986) ; ce virus est semblable à celui qui est responsable de la maladie mortelle observée de manière prédominante dans l'espèce asiatique et particulière-ment chez les jeunes animaux : il est dénommé ElHV1 (Richman et al 1999 ;Welleham et al 1998). Une troisième espèce d'herpèsvirus a été récemment étudiée chez des éléphants d'Asie (Garner et al 2009 et al 1971).…”
Section: Herpèsvirus D'éléphantsunclassified
“…Ultérieurement, ce virus a été nommé elephantid herpesvirus 2 (ElHV2). Un autre herpèsvirus fut ensuite associé à des papillomes cutanés chez l'élé-phant d'Afrique (Jacobson et al 1986) ; ce virus est semblable à celui qui est responsable de la maladie mortelle observée de manière prédominante dans l'espèce asiatique et particulière-ment chez les jeunes animaux : il est dénommé ElHV1 (Richman et al 1999 ;Welleham et al 1998). Une troisième espèce d'herpèsvirus a été récemment étudiée chez des éléphants d'Asie (Garner et al 2009 et al 1971).…”
Section: Herpèsvirus D'éléphantsunclassified
“…A precedent is that humans are hosts to three alphaherpesviruses, herpes simplex viruses 1 and 2, and varicella-zoster virus (formally, Human herpesviruses 1, 2, and 3). Although there were early suggestions that severe hemorrhagic disease associated with EEHV1 was due to infection of Asian elephants with virus from African elephants (13), accumulated evidence shows that these viruses can cause disease as well as persist asymptomatically in their native hosts. While EEHV1 is thus far the major pathogen, the presence of multiple closely related host-specific viruses will complicate efforts to develop vaccines and therapeutic approaches.…”
Section: Genomic Plasticity and Diversitymentioning
confidence: 99%
“…With very few exceptions, the amino acid sequence of a small conserved segment of the viral DNA polymerase (ϳ150 amino acids) is sufficient to not only reliably identify a virus as belonging to the evolutionary lineage represented by the Herpesviridae, but also their subfamily, and in most cases a recognized genus. Early analyses of such sequences from EEHV1 showed that sequences of its DNA polymerase and other highly conserved herpesvirus core genes branched near the base of the betaherpesvirus branch of the herpesvirus tree, leading to the suggestions that the virus might represent a new herpesvirus subfamily (13,14). EEHV1 is currently formally recognized as the species Elephantid herpesvirus 1, the type species in the Proboscivirus genus within the Betaherpesvirinae.…”
Section: A New Herpesvirus Subfamily?mentioning
confidence: 99%
“…Microbes are frequently non-pathogenic in their natural host species and lethal in their new host. Myxoma virus in American cottontail rabbits became deadly and epidemic in European rabbits (Fenner 1988); a mild herpesvirus infection of African elephants kills Asian elephants and possibly vice versa (Richman et al 1999); and herpesvirus B of rhesus monkeys causes lethal encephalopathy in humans (Palmer et al 1998). SIVsm appears harmless in sooty mangabey monkeys yet causes AIDS in humans.…”
Section: Zoonosis and Virulencementioning
confidence: 99%